Guillain-Barré syndrome associated with the Zika virus outbreak in Brazil - Lucas Masiêro Araujo; Maria Lucia Brito Ferreira; Osvaldo JM Nascimento (Arquivos de Neuro-Psiquiatria, 2016)
ABSTRACT Zika virus (ZIKV) is now considered an emerging flavivirosis, with a first large outbreak registered in the Yap Islands in 2007. In 2013, a new outbreak was reported in the French Polynesia, with associated cases of neurological complications including Guillain-Barré syndrome (GBS). The incidence of GBS has increased in Brazil since 2015, what is speculated to be secondary to the ZIKV infection outbreak. The gold-standard test for detection of acute ZIKV infection is the polymerase-chain reaction technique, an essay largely unavailable in Brazil. The diagnosis of GBS is feasible even in resource-limited areas using the criteria proposed by the GBS Classification Group, which is based solely on clinical grounds. Further understanding on the relationship of ZIKV with neurological complications is a research urgency.